2018
DOI: 10.1017/s0030605318001333
|View full text |Cite
|
Sign up to set email alerts
|

Earth Optimism—recapturing the positive

Abstract: On Earth Day weekend , Earth Optimism summits and related events around the world celebrated conservation success stories. In Washington, DC, over  presentations featured progress in protecting species and spaces, reducing pollution, restoring habitats, harvesting wisely, and tackling climate change (EarthOptimism, ). Participants included not only conservation scientists, but also policy makers, students, artists, engineers, inventors, and representatives of business, media and philanthropy. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…However, although conservation successes do occur (e.g. Halley & Rosell, 2002; Balmford, 2017; Knowlton, 2019), highlighting the importance of conservation action, continued monitoring is required. Whilst species may return to areas where they were previously extirpated, many populations remain below historical abundance levels and do not reach the numbers necessary to secure long-term survival (Deinet et al, 2013).…”
mentioning
confidence: 99%
“…However, although conservation successes do occur (e.g. Halley & Rosell, 2002; Balmford, 2017; Knowlton, 2019), highlighting the importance of conservation action, continued monitoring is required. Whilst species may return to areas where they were previously extirpated, many populations remain below historical abundance levels and do not reach the numbers necessary to secure long-term survival (Deinet et al, 2013).…”
mentioning
confidence: 99%
“…We particularly draw on the extensive body of literature showing that virtually all aspects of cognition are affected by emotion (Jacobs, 2012), including perception (Dolan, 2002), motivation (Izard, 2009) and decision-making (Winkielman et al, 2007) Promote positive messaging: It has been reported that people are generally willing to donate more money and time to conservation organizations associated with positively framed messages (Filep & Laing, 2019;Jacobson et al, 2019). This sits well within the growing academic literature flagging the importance of well-informed optimism in motivating societal change towards sustainability (Balmford, 2017;Balmford & Knowlton, 2017;Knowlton, 2018).…”
Section: Embark Ing On a Ne W Chap Ter Of Con S Ervati On Me Ssag Ingmentioning
confidence: 88%
“…While reducing global carbon emissions is accepted as essential to support coral reef survival into the 21st century, there is much debate about the role of different local-and regional-level management interventions. This has led to recent advocacy efforts to avoid portraying an exclusively "doom and gloom" picture of the future of coral reefs (Abelson, 2020), and to instead promote ocean optimism (Knowlton, 2018). This can be achieved, for example, by highlighting appropriate management interventions (e.g., proper sewage treatment, effective fisheries management) that local decision-makers can take to enhance reef resilience and support reef conservation (Abelson, 2020).…”
Section: Changing Priorities Of Reef Science and Conservationmentioning
confidence: 99%